Design, operation and evaluation of an improved refractory wear testing technique. (June 2021) - Kircher, Volkmar; Burhanuddin,; Harmuth, Harald
Graphical abstract: Highlights: New dynamic laboratory corrosion test based on a rotating cylinder specimen. Dynamic and static corrosion experiments. In-situ wear rate measurement of fine ceramic dissolution in slags. High precision 3D laser measurement system using laser line triangulation. Abstract: A newly developed Continuous Wear Testing Device (CWTD) based on a rotating cylinder specimen enables in-situ wear rate measurements of fine ceramic dissolution in slags. A corroding fine ceramic sample is measured several times during a corrosion test with a high precision 3D laser measurement system. Mass loss derived from this measurement is compared with direct determination by load cells. Optimal flow conditions for static and dynamic measurements are achieved by a high ratio of slag mass to immersed sample mass and by an adjustable rotation speed. Corrosion of Al2 O3 fine ceramic cylinders in a CaO-MgO-Al2 O3 -SiO2 slag at 1550 °C demonstrated the occurrence of Marangoni convection and lower corrosion rate for a static measurement, while Taylor vortices appeared with a dynamic setup. The accuracy of the wear measurement was assessed and evaluated for corrosion profiles which enable the identification of kinetic models for the calculation of diffusivities.